(untitled) (Global Journal of Medical Research, 2024)
Space weather is the term used to describe events, or storms, in space that affect humans. These events, including solar flares, coronal mass ejections, and their associated electromagnetic effects, are primarily attributed to magnetic shifts occurring on the Sun. These events intensify during solar maximum, the phase of the 11-year solar cycle leading up to the Sun’s polar shift, during which the Sun’s magnetic north and south poles switch. The resulting geomagnetic storms reach and affect Earth’s atmosphere, with impacts on electrical systems, including power infrastructure, communications systems, and biological systems. Epidemiological studies show correlations between solar activity and increased severity of neurologic symptoms, increased rates of cardiovascular events, and behavioural, immune, and other effects. Currently, the Sun is approaching solar maximum, which will peak in 2025, bringing an increased frequency and intensity of geomagnetic storms.